Clinical teaching competencies training program for nurse teachers and its effect on their self-esteem - Mustafa, Asmaa S.; Shazly, Mona M.; Kalaaf, Dalia Atef (Frontiers in Education, 2025)
BackgroundClinical teaching competencies are fundamental for nurse educators, as they play a crucial role in enhancing the self-esteem of nurse teachers within clinical settings.ObjectivesThe aim of the study was to assess the training program to improve the clinical teaching competencies of nurse teachers and to evaluate its effect on their self-esteem.MethodsA quasi-experimental design was employed, involving all available nurse teachers (N = 50) from the Technical Institute of Nursing, Faculty of Nursing, Ain Shams University, Cairo, Egypt. A total of three tools were utilized: (1) a knowledge questionnaire on clinical teaching competencies, (2) an observational checklist for clinical teaching competencies, and (3) the Rosenberg self-esteem scale.ResultsThere was a highly significant improvement in the knowledge and performance of the nurse teachers in relation to clinical teaching competencies. Knowledge scores increased to 100% in both the immediate post-training and follow-up phases, while performance scores improved to 96.0% in the immediate post-training phase and 60.0% in the follow-up phase. In addition, the majority of the nurse teachers (64%) demonstrated a high level of self-esteem immediately after the training program, and 62.0% maintained a high level in the follow-up phase, compared to only 4.0% before the training program.ConclusionThere was a highly statistically significant positive correlation between total knowledge, performance related to clinical teaching competencies, and the self-esteem of nurse teachers in the immediate post-training program phases. In addition, there was a statistically significant positive correlation between total knowledge, performance related to clinical teaching competencies, and the self-esteem of nurse teachers in the follow-up phase.